The Shared Customer Collaboration Vehicle Routing Problem - Fernández, Elena; Roca-Riu, Mireia; Speranza, M. Grazia (European journal of operational research, 2018)
•We introduce the Shared Customer Collaboration Vehicle Routing Problem.•There are potential savings when carriers collaborate to serve shared customers.•Two alternative formulations are proposed and analyzed.•Extensive computational experiments are provided.•We quantify the potential benefits compared to the case when no collaboration exists. This paper introduces a new vehicle routing problem that arises in an urban area where several carriers operate and some of their customers have demand of service for more than one carrier. The problem, called Shared Customer Collaboration Vehicle Routing Problem, aims at reducing the overall operational cost in a collaboration framework among the carriers for the service of the shared customers. Alternative mathematical programming formulations are proposed for the problem that are solved with a branch-and-cut algorithm. Computational experiments on different sets of benchmark instances are run to assess the effectiveness of the formulations. Moreover, in order to estimate the savings coming from the collaboration, the optimal solutions are compared with the solutions obtained when carriers work independently from each other.